The Determination of cadmium levels in corn grains (Zea mays L.) from the Ecuadorian coast and mountains (Revista Científica Ciencias Naturales y Ambientales, 2018)
Concentrations of Cd were determined in corn grains harvested on coast and sierra of Ecuador, six varieties of greater consumption have been chosen for analysis: sweet, dent, popcorn, morocho, chulpi and white. For each variety, the samples were taken in triplicate (n=3), besides were processed and analyzed by Graphite Furnace Atomic Absorption Spectrophotometry. The six varieties presented concentrations below the maximum permissible limit (0.1 mg/kg) established by the European Union, the Codex Alimentarius and the INEN 187:2013. In the comparative analysis by regions, average levels of Cd are higher in the sierra (0.019 mg / kg) than in the coast (0.006 mg / kg Cd). There were no statistically significant differences between varieties (p > 0.05). The highest concentration of Cd was obtained by the morocho (0.025 ± 0.022 mg / kg Cd) and the lowest by the sweet variety (0.001 ± 0.000 mg / kg Cd). It was evidenced that the concentrations of Cd are directly related to the days of harvest and the altitude at which they are grown. In addition, a proposal to mitigate or decrease the contamination by Cd in agricultural soils has been presented.
Keywords: bioaccumulation; cadmium; corn grains; Ecuador; Zea mays